MENINGKATKAN HASIL BELAJAR SENI BUDAYA MATERI SENI RUPA MELALUI METODE PEMBELAJARAN TUTOR SEBAYA PADA SISWA KELAS VIII B SMP 1 BUKITTINGGI - Ridwan, Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2019)
The research objectives to be achieved in this study were to improve the learning outcomes of Cultural Arts in Fine Arts material for students of class VIII B SMP 1 Bukittinggi with the application of peer tutoring learning methods. This research is classroom action research and observation. Data usage techniques used are tests and observations. Based on the coefficients table, the value of t count of the cycle I -0.885 is smaller than t table and t count of cycle II -2.145 is greater than t table which is 0.040 then the hypothesis is rejected. So it can be concluded that the use of the Peer Tutor Learning method has a significant effect on the learning outcomes in Art Culture lessons in Art material at SMP 1 Bukittinggi. Then H0 is rejected and H1 is accepted. Based on the description above, it can be concluded that the use of peer tutoring learning methods to improve student learning outcomes in learning arts and culture at SMP 1 Bukittinggi .Keywords: peer tutoring, learning outcomes